A poesia de Teócrito e a projeção pastoral - Alexandre Cardoso Nunes Magalhães (2021)
Theocritus is the founder of the pastoral genre. This research seeks to analyze the bodywork of the author, starting from the privileged reading that a translation process provides, to better establish the status of pastoral representation that the idylls could have. After minimally presenting the author’s life and work, the history of his texts’ transmission and the dialect used by him, we have a translation of all his idylls currently considered authentic, including a brief introductory note that tries to make more accessible the essential content of each translated idyll. To address the issue of pastoral representation, we introduce a study on the issue of literary genres and their origins, dealing more specifically with the pastoral genre, its importance and how its foundations are presented in his work through examples. We then expose the specific point of pastoral representation in the idylls, starting with the ancient doctrine of mimesis as it was written by Plato and Aristotle, and how it could minimally frame the Theocritian work. Having thus clarified mimesis in the rural context, we can propose the concept of pastoral projection, and how it can help to clarify the author’s poetic program, the reading of his work and the general perception of its poetic effects by stating how the poet makes a projection similar to the ones that the characters themselves perform within the poems. The research was also mobilized in order to make the idylls more accessible, offering comments and examples that benefit the understanding of the work as a whole.